ANALISIS EKSEKUSI PIDANA UANG PENGGANTI PADA KORPORASI BUMN YANG TIDAK DIJADIKAN SEBAGAI TERDAKWA (STUDI KASUS MAHKAMAH AGUNG NO. 1964 K /PID.SUS/2015) - Andi Sabputera; Firman Wijaya (Jurnal Hukum Adigama, 2019)
Corruption has become a quite serious problem faced by the Indonesian nation, especially corruption involving BUMN, one of which is the involvement of state-owned corporation PT NK in corruption cases for the construction of the Sabang pier in 2014 to 2011 which has cost the state finances Rp.798 billion. The defendant in this case was HS  as the Branch Head, but the corporation was never appointed as a defendant. Based on the results of the analysis that although the state-owned corporation PT NK corroboration was not prosecuted in the indictment, the court ruling imposes responsibility for paying substitute money. This is in accordance with the judgment of the judge due to the receipt of money from the corruption crimes that enter the corporation so that additional penalties in the form of substitute money can be imposed on PT NK. Execution of criminal money substitute for corruption cases, KPK prosecutors can confiscate and auction off corporate assets. If the asset has been sold, the prosecutor can file for bankruptcy and if the corporation claims to be unable to pay substitute money, then the prosecutor needs to trace the assets of the corporation concerned. In the case of state-owned corporation PT NK still having the obligation to pay substitute money, it would be difficult to analyze because the KPK found it difficult to handle it because it involved state finances. The implication is that if a BUMN corporation cannot pay substitute money then the return on state financial losses is not optimal.